IGIST - A Kinetic Bioassay for Pertussis Toxin Based on Its Effect on Inhibitory GPCR Signaling - Valeriy M. Paramonov; Cecilia Sahlgren; Adolfo Rivero-Müller; Arto T. Pulliainen (American Chemical Society, 2022)
Detection of pertussis toxin (PTX) activity is instrumental for the development and manufacturing of pertussis vaccines. These quality and safety measures require thousands of mice annually. Here, we describe Interference in Gαi-mediated Signal Transduction (iGIST), an animal-free kinetic bioassay for detection of PTX, by measuring its effect on inhibitory G protein-coupled receptor (GPCR) signaling. PTX ADP-ribosylates inhibitory α-subunits of the heterotrimeric G proteins, thereby perturbing the inhibitory GPCR signaling. iGIST is based on HEK293 cells coexpressing a somatostatin receptor 2 (SSTR2), which is an inhibitory GPCR controllable by a high-affinity agonist octreotide; and a luminescent 3′5′-cyclic adenosine monophosphate (cAMP) probe. iGIST has a low sensitivity threshold in the pg/mL range of PTX, surpassing by 100-fold in a parallel analysis the currently used in vitro end-point technique to detect PTX, the cluster formation assay (CFA) in Chinese hamster ovary cells. iGIST also detects PTX in complex samples, i.e., a commercial PTX-toxoid-containing pertussis vaccine that was spiked with an active PTX. iGIST has an objective digital readout and is observer independent, offering prospects for automation. iGIST emerges as a promising animal-free alternative to detect PTX activity in the development and manufacturing of pertussis vaccines. iGIST is also expected to facilitate basic PTX research, including identification and characterization of novel compounds interfering with PTX.